In vivo antigenotoxic activity of watercress juice (Nasturtium officinale) against induced DNA damage - Casanova, Natalia Andrea (2013)
The present study was carried out to investigate the genotoxicity as well as possible protective activity against damage induced by cyclophosphamide (CP) of the aqueous juice of watercress (Nasturtium officinale, W.T. Aiton) in vivo. Male and female Swiss mice 7-8 weeks old (N = 48) were treated by gavage with 1 g kg(-1) body weight and 0.5 g kg(-1) body weight of watercress juice during 15 consecutive days. Genotoxicity and its possible protective effect were tested by the comet assay in peripheral blood cells and the micronucleus test in bone marrow. In addition, biopsies of the bladder, epididymis and testicles of mice were performed to extend the experimental design. Watercress juice per se did not induce genetic damage according to the comet assay and micronucleus study, exhibiting a protective activity against CP (P < 0.05 and P < 0.001, respectively). The comparative analysis of bladder histological changes obtained in the watercress plus CP group against those treated with CP alone suggests a probable protective effect. Further studies are needed in order to establish the protective role of watercress juice against DNA damage.